Smartphone-based Robot Design Training with Voice Control for Senior High School in Tasikmalaya City - Sambas, Aceng; Gundara, Gugun; Ayob, Ahmad Faisal bin Mohamad; Andriana, Aan; Aziz, Faisal Abdul (International Journal of Ethno-Sciences and Education Research, 2022)
The main objective of this work is to provide training to build smart phone-based smart robots with voice control to teachers at Senior High Schools, Tasikmalaya City, Indonesia. This robot consists of various electronic components such as Arduino, IC L293D, Bluetooth Module HC05, dynamo, gear box and battery. In addition, we have used several software to build intelligent robots such as Arduino software for uploading a command and AMR voice application for controlling via voice commands. The results showed that the teachers had succeeded in making robots with voice control for forward and backward commands with the help of the AMR voice application. In addition, the results of this training are expected to increase the creativity of teachers in the learning process and as teaching materials to create an active and collaborative class.